Bone Turnover in Postmenopausal Women with Bone Loss - Original Investigation - Nurdan Paker; Burcu Sarıca Mutlu; Demet Tekdöş; Betül Kaya; Derya Soy Buğdaycı (Galenos Yayinevi, 2005)
Osteoporosis is characterized by decrease in bone strength due to decreased bone mass and disruption of bone microstructure and eventually increase in fracture risk. Increased bone turnover in postmenopausal period results in bone loss and osteoporosis. Aim of our study was to investigate the rate of bone turnover in postmenopausal women. Postmenopausal women were included in this study. Dual energy X ray absorbtiometry( Dexa) was used for the measurement of BMD of the lumbar spine and proximal femur. Serum osteocalcin and type 1 collagen cross-linked C-telopeptide (Ctx) levels were measured in blood. 32 postmenopausal women with bone loss were included in our study. The mean age was 61,5 ± 9,6 years, mean menopause duration 14,7± 9,5 years. The mean value of L2- L4 BMD was 0,910 ±0,143 gr/cm2 , femur neck BMD 0,734± 0,134 gr/cm2. Mean blood osteocalcin level was 23,34± 10,9 ng/ml(normal range <20), Ctx level was 0,70± 0,27 (normal range <0.75) ng/ml. There was statistically significant negative relationship between the menopause duration and serum Ctx levels (R =0,382, p<0,05). Mean serum Ctx level was 0,83 ±0,11 ng/ml in the patients whose menopause duration was less than 5 years and was 0,7 ±0,3 ng/ml in the patients whose menopause duration was more than 5 years. There was no relationship between serum osteocalcin and Ctx levels with age, body mass index(BMI), menopause duration, L2- L4 and femur neck BMD values. There was statistically significant relation between BMI(body mass index) and L2 - L4 and femur neck BMD values( p < 0.05). There was no relationship between regular walking activity with BMD, serum osteocalcin and Ctx levels. In this study increased bone turnover rate in early postmenopausal period has been shown. It was known that bone loss increases due to the estrogen deficiency in postmenopausal period. Therefore, bone turnover markers of postmenopausal women should be measured in addition to bone mineral density who had bone loss to determine women with increased bone loss in order to prevent and to treat osteoporosis. (Osteoporoz Dünyasından 2005; 4: 155-158)